2019
DOI: 10.17148/iarjset.2019.61204
|View full text |Cite
|
Sign up to set email alerts
|

https://iarjset.com/wp-content/uploads/2019/12/IARJSET.2019.61204.pdf

Abstract: In this paper, the importance of using and utilizing technical methods to improve marketing and customer relationship management is presented. Among the many patterns, theories and programs, the decision support system processes are proposed by Markov.Finally, discuss the use of the Markov model in marketing and customer service

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 10 publications
(16 reference statements)
0
15
0
2
Order By: Relevance
“…Leakage occurs when the perpetrators make their intentions known prior to the attack and may be written or verbal. Estimates of leakage that occurs in all mass public shootings ranges from around 30% to 40% in other work (Capellan & Gomez, 2018; Capellan & Jiao, 2019; Duwe, 2020, but see a higher estimate in Lankford et al, 2019).…”
Section: Mass Public Shootingsmentioning
confidence: 85%
See 1 more Smart Citation
“…Leakage occurs when the perpetrators make their intentions known prior to the attack and may be written or verbal. Estimates of leakage that occurs in all mass public shootings ranges from around 30% to 40% in other work (Capellan & Gomez, 2018; Capellan & Jiao, 2019; Duwe, 2020, but see a higher estimate in Lankford et al, 2019).…”
Section: Mass Public Shootingsmentioning
confidence: 85%
“…While developing mass public shooter profiles remains problematic because they often fail to differentiate between people likely to commit mass shootings and those who are not (Schildkraut et al, 2019), characteristics of the incident, including how it was carried out, may point to possible intervention points (Capellan & Jiao, 2019). For example, Capellan and Jiao (2019) found that about half of perpetrators were seeking revenge, and there was a clear precipitant. Leakage occurs when the perpetrators make their intentions known prior to the attack and may be written or verbal.…”
Section: Mass Public Shootingsmentioning
confidence: 99%
“…Besides, to evaluate the ASD‐oriented requirement of safe driving operations, that is, the ASD must be greater than or at least equal to the RSD [75, 76], the RSD for LAVs needs to be calculated. According to the classification of driving automation levels proposed in [1] and professional investigations [77] of the sensor configuration of commercially available or test AVs, possible levels for LAVs include conditional (level 3, L3), high (level 3, L4), and full (level 5, L5) automation due to the utilization of LiDAR‐based perception system.…”
Section: Available Sight Distance Analysismentioning
confidence: 99%
“…The percentage of waste composition in the West Bank is nearly identical to that in the Gaza Strip. The composition of waste is illustrated in Exhibit 1 (GIZ, 2014; Thöni & Matar, 2019). As shown in the graph, about half of the waste composed of organic material, making the potential for methane recovery from this waste exceptionally significant.…”
Section: Introductionmentioning
confidence: 99%